Recent advances in the development of sources of resistance to pink stalk borer and African sugarcane borer - Bosque Pérez, N.A.; Kling, J.G.; Odubiyi, S.I. (1997)
The lepidopterous stem borers Sesamia calamistis Hampson (Noctuidae) and Eldana saccharina (Walker) (Pyralidae) are among the most important insect pests of maize in West Africa. Efforts to breed for resistance to these two borer species are an integral part of a project to develop control practices for maize pests at IITA. Since 1985, a wide diversity of maize germplasm has been evaluated for resistance to either S. calamistis or E. saccharina. Three populations with moderate resistance to E. saccharina (TZBR Eldana 1, 2, and 3) and two with moderate resistance to S. calamistis (TZBR Sesamia 1 and 3) were formed in the late 1980's and are being improved for adaptation and resistance levels primarily through S1 family testing. The populations are intended as sources of resistance to be used by African national breeding programs, as well as by colleagues in other parts of the world. TZBR Eldana 3 was developed from elite, adapted populations and has performed well in multilocational yield trials in Nigeria and Cote d' Ivoire. TZBR Eldana 1 was derived from exotic germplasm and is less adapted to the lowland humid tropics. A selection index which combines agronomic characteristics and E. saccharina resistance, is used to improve the TZBR Eldana populations. Cycles of selection trials with these populations have shown continual progress in selecting for resistance to E. saccharina. Of the two Sesamia populations, TZBR Sesamia 3 appears to have higher levels of resistance than TZBR Sesamia 1. Future selection will be based on improved agronomic characteristics and disease resistance levels, concurrent with higher levels of resistance to S. calamistis.